The Effect of the Arousal Dimension of Jazz Instrumental Music on Selective Attention in College Students - Ahmad Insanu Firmansyah; Indra Kusuma Wardani (Graduate School of Institut Seni Indonesia Yogyakarta, 2026)
Selective attention is increasingly challenged by distractions in modern higher education, and while instrumental music has been proposed as its aid, findings remain mixed. This study aimed to examine the effect of jazz instrumental music on selective attention compared to silence, and whether its jazz ballad (low-arousing music) and bebop (high-arousing music) styles differ in their effects—a distinction not previously investigated experimentally. Using a true experimental approach and pretest-posttest design, 40 college students were randomly assigned to either the jazz ballad or bebop group. Selective attention was measured via response time (RT) and error rate (ER) from a Stroop Test, with EEG attention scores as complementary neurophysiological indicators. Both groups showed significant within-group RT reductions relative to silence. However, only the jazz ballad group showed a significant ER reduction (p = .040), whereas the bebop group did not (p = .119), despite its significantly higher posttest between-group EEG attention scores (p = .001). No significant between-group differences were found for RT or ER. Drawing primarily on Late Selection Theory and Kahneman's Capacity Model, these findings suggest that the moderate arousal from low-arousing music may more optimally facilitate selective attention than higher arousal or increased alertness alone from high-arousing music.Pengaruh Dimensi Arousal Musik Instrumental Jazz terhadap Atensi Selektif pada Mahasiswa Abstrak Atensi selektif semakin terganggu oleh bermacam distraksi dalam pendidikan tinggi modern. Meskipun musik instrumental telah ditawarkan sebagai penopangnya, temuan-temuannya masih inkonsisten. Penelitian ini bertujuan untuk menguji perbedaan pengaruh musik instrumental jazz terhadap atensi selektif dibandingkan kondisi hening, serta perbedaan pengaruh antara gaya jazz ballad (musik low-arousing) dan bebop (musik high-arousing)—suatu perbedaan yang belum pernah diteliti secara eksperimental. Menggunakan pendekatan true experimental dan desain pretest-posttest, 40 mahasiswa secara acak dibagi ke grup jazz ballad atau bebop. Atensi selektif diukur via response time (RT) dan error rate (ER) dari Stroop Test, dengan skor atensi EEG sebagai indikator neurofisiologis komplementer. Kedua grup menunjukkan penurunan signifikan RT pada analisis within-group dibandingkan kondisi hening. Namun, hanya grup jazz ballad yang menunjukkan penurunan signifikan ER (p = .040), sedangkan grup bebop tidak (p = .119), kendati skor atensi EEG between-group posttest-nya signifikan lebih tinggi (p = .001). Tidak ditemukan perbedaan signifikan RT maupun ER pada analisis between-group. Mengacu utamanya pada Late Selection Theory dan Kahneman's Capacity Model, temuan ini mengindikasikan bahwa arousal moderat dari musik low-arousing berpotensi lebih memfasilitasi atensi selektif secara optimal daripada sekadar arousal yang lebih tinggi atau alertness yang meningkat dari musik high-arousing.